The Influence of Intrinsic Motivation, Workload Competence, and Competency on Advocate Performance Through Job Satisfaction as an Intervening Variable in the Indonesian Advocates Association Advocate Joint House (Peradi Rba) - Rita Rosita Dewi; Suryono Efendi (International Forum of Researchers and Lecturers, 2025)
This study investigates the impact of intrinsic motivation, workload, and competence on job satisfaction, exploring its implications for employee performance, with job satisfaction serving as a mediating variable. A quantitative approach was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis collected via questionnaires. The results reveal that intrinsic motivation has a positive but insignificant impact on job satisfaction and performance. Workload significantly improves job satisfaction but does not affect performance, while competence significantly enhances both job satisfaction and performance. Additionally, job satisfaction positively affects employee performance. The mediation analysis reveals that job satisfaction mediates the relationship between competence and workload on performance, but does not mediate the relationship between intrinsic motivation and performance. These findings highlight the critical roles of competence and job satisfaction in improving employee performance, suggesting that intrinsic motivation and workload may require additional factors, such as compensation and work environment, to be more effective.